2001
DOI: 10.1006/mvre.2001.2349
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Actin Cytoskeleton on Intra-articular and Interstitial Fluid Pressures in Synovial Joints

Abstract: Fibroblast microfilamentous actin (F-actin) influences interstitial fluid pressure via linkages to collagen in rat skin (Berg et al., 2001). The present aims were to determine whether the actin cytoskeleton of synovial endothelium, fibroblasts, and synoviocytes influences in vivo (i) fluid exchange between a joint cavity and synovial microcirculation and (ii) extracellular fluid pressures in joints. Rabbit knee joints were treated intra-articularly with the Factin disrupting drugs cytochalasin D and latrunculi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 44 publications
2
26
1
Order By: Relevance
“…The study extends a recent investigation of changes in intra-articular pressure and matrix interstitial pressure following F-actin disruption (40). The latter investigation indicated that actin disassembly raised capillary filtration rate and ␥-globulin permeation, but that synoviocyte F-actin disassembly had no detectable effect on interstitial fluid pressure post mortem, in contrast to the findings of Berg et al (5) in rat skin.…”
Section: Introductioncontrasting
confidence: 54%
“…The study extends a recent investigation of changes in intra-articular pressure and matrix interstitial pressure following F-actin disruption (40). The latter investigation indicated that actin disassembly raised capillary filtration rate and ␥-globulin permeation, but that synoviocyte F-actin disassembly had no detectable effect on interstitial fluid pressure post mortem, in contrast to the findings of Berg et al (5) in rat skin.…”
Section: Introductioncontrasting
confidence: 54%
“…It may, however, not be a general mechanism for edema formation, since there was no effect on P if in the rabbit synovium after disrupting the cytoskeleton by cytochalasin D treatment, although resulting in hyperfiltration into the joint mimicking an inflammatory reaction (368).…”
Section: Interstitial Pressure and Flow In Inflammation And Injurymentioning
confidence: 96%
“…Endothelial cells adapt to shear flow by forming extended Factin stress fibers that align in the direction of flow (Girard and Nerem, 1995;Langille et al, 1991;Malek and Izumo, 1996) and polarize by reorganizing the microtubule network to reposition the centrosome in the direction of flow (Tzima et al, 2003;Wojciak-Stothard and Ridley, 2003). Shear flows also cause changes in actin and microtubule structures in myofibroblasts and fibroblasts (Lee et al, 2005;Ng et al, 2005;Ng and Swartz, 2003;Poli et al, 2001), and influence their nuclear-receptor distributions and nucleus movement (Ji et al, 2003;Tseng et al, 2004). Reorganizations of cytoskeletal structures in endothelial cells and fibroblasts are coupled to the activity of members of the Rho GTPase family, including RhoA, Rac1 and Cdc42 (Hall, 1998;Nobes and Hall, 1995;.…”
Section: Introductionmentioning
confidence: 99%